Soil and Environmental Science Dictionary - Gregorich, Ed (CRC Press, 2009)
The lingo of soil science is a language unto itself. Soil and Environmental Science Dictionary is a glossary of terms used in soil and environmental science, including terms from related disciplines. Designed for teachers, students, researchers and others interested or involved in environmental sciences related to soils, this compilation includes all terms and definitions from the current Canadian Society of Soil Science (CSSS) glossary as well as from various other sources such as the Soil Science Society of America and the Soil and Water Conservation Society. Soil and Environmental Science Dictionary defines terms accurately and clearly for professionals working in areas such as agronomy, building construction, civil engineering, forestry, environmental science and planning, geology, hydrology, petrology, and plant science.